Preparation and absorption properties of poly (acrylic acid‐co‐acrylamide)/graphite oxide superabsorbent composite. Issue 8 (22nd November 2018) - Zhu, Linhui; Wang, Fangyuan; Liu, Yu; Tang, Hongduo; Guan, Chengdong
Abstract: Poly (acrylic acid‐co‐acrylamide)/graphite oxide (P (AA‐co‐AM)/GO) superabsorbent composite was prepared by solution intercalation polymerization of acrylic acid (AA), acrylamide (AM), and graphite oxide (GO). The composite was characterized by Fourier transform infrared spectroscopy, powder X‐ray diffraction, scanning electron microscopy, transmission electron microscope, thermogravimetric analysis, and differential scanning calorimetry. The effect of reaction conditions, including the mass ratio of monomers, dosages of cross‐linker, initiator, and GO as well as the neutralization degree of AA, on water and saline absorption was studied. Water retention properties of the composite were also discussed. It showed that interactions between GO and P (AA‐co‐AM) copolymer were the intermolecular hydrogen bonds. Thermal stabilities of the composite could be improved by the incorporation of GO. Besides, there was a remarkable improvement of absorption capacities owing to the incorporation of GO. Absorption capacities of water and 0.9% NaCl could be improved from 141.7 and 33.6 g/g, respectively, to 809.6 and 131.4 g/g, respectively, as the dosage of GO increased from 0 to 0.1 g. In addition, there was a remarkable improvement of water retention rates. Water retention rates of P(AA‐co‐AM)/GO and P(AA‐co‐AM) were 65.9% and 53.8%, respectively, after drying at 25°C for 8 hr.